INNOVATIVE POTENTIAL OF SMALL AND MEDIUM-SIZED ENTERPRISES: ESSENCE AND CHARACTERISTICS - GRYNKO, Tatyana; BAZYK, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article highlights current issues regarding the potential of small and medium-sized enterprises (SMEs), which is an important factor in the economic development of any country. The innovative potential of the enterprise is the ability of the organization to generate new ideas and implement them in its activities. This is a complex indicator that includes various aspects that affect a company's ability to be innovative. The study provides key aspects that determine the innovative potential of SMEs, namely: economic growth - SMEs contribute to the creation of new jobs and ensure the flexibility of the economy, as they quickly respond to market changes; innovation – small and medium-sized enterprises are often the source of new ideas and technologies, as they have lower bureaucratic barriers and more flexible structures; competition - SMEs contribute to increasing the level of competition in the market, which stimulates large companies to increase efficiency and improve the quality of products and services; social aspect – small and medium-sized enterprises are often the basis for the development of local communities, providing jobs and supporting the local economy; globalization – SMEs can successfully enter international markets, contributing to the country's export potential. Key challenges for SMEs include access to finance, regulatory barriers, shortages of skilled workers and the need to adapt to technological change. Support from the state, business incubators and other organizations can significantly improve the conditions for the development of small and medium-sized enterprises. An up-to-date analysis of small and medium-sized enterprises was carried out and the corresponding steps for creating an effective innovation potential of small and medium-sized enterprises were provided. The key elements of innovation potential are presented, namely: resource base, organizational structure and culture, research and development (R&D), information support, patent and licensing activities, innovation marketing, innovation management. Innovative potential is a key factor for ensuring long-term competitiveness and success of the enterprise on the market. It allows the company not only to respond to changes in the external environment, but also to actively form new market opportunities.
Keywords: innovation; competitiveness; small and medium enterprises; potential; resources